2008
DOI: 10.1093/eurheartj/ehn341
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation in stroke-free patients is associated with memory impairment and hippocampal atrophy

Abstract: Even in the absence of manifest stroke, AF is a risk factor for cognitive impairment and hippocampal atrophy. Therefore, cognition and measures of structural brain integrity should be considered in the evaluation of novel treatments for AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
173
1
25

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(217 citation statements)
references
References 48 publications
7
173
1
25
Order By: Relevance
“…For some evidences, an atrial fibrillation was relevant to cognitive impairment and hippocampal atrophy with no symptomatic stroke or silent infarction. 34,35 The previous studies 26,30,31,[36][37][38][39] and the results of our study have shown that atrial fibrillation was associated with an increased risk of poststroke dementia. Moreover, the result of this study found that stroke patients with atrial fibrillation risk of dementia were 1.68 times compared with stroke patients without atrial fibrillation statistically significant.…”
Section: Discussionmentioning
confidence: 50%
“…For some evidences, an atrial fibrillation was relevant to cognitive impairment and hippocampal atrophy with no symptomatic stroke or silent infarction. 34,35 The previous studies 26,30,31,[36][37][38][39] and the results of our study have shown that atrial fibrillation was associated with an increased risk of poststroke dementia. Moreover, the result of this study found that stroke patients with atrial fibrillation risk of dementia were 1.68 times compared with stroke patients without atrial fibrillation statistically significant.…”
Section: Discussionmentioning
confidence: 50%
“…Although the clinical relevance of these DWI lesions remains uncertain, they may cause decline in cognitive function as suggested by previous reports on silent cerebral lesions involving patients other than the typical TAVR patients [11,12,22]. For instance, the population-based Rotterdam Scan Study showed that elderly people with silent brain infarcts have an increased risk of dementia and a steeper decline in cognitive function than those without such lesions [11,12,22]. Therefore, based on these previous reports, the high frequency of ischemic lesions on post-TAVR cerebral imaging calls for procedural and technical developments to reduce the risk of peri-procedural embolization.…”
Section: Discussionmentioning
confidence: 89%
“…Although the consequences of silent ischemic brain lesions are still uncertain, in some studies they have been associated with cognitive decline and an increased risk of dementia and depression [11][12][13]. Furthermore, they have been shown to indicate an increased risk of subsequent stroke in patients with previous minor stroke and atrial fibrillation [13].…”
Section: Introductionmentioning
confidence: 99%
“…U pacjentów z AF często stwierdza się zmiany w istocie białej mózgu, zaburzenia czynności poznawczych [28][29][30], pogorszenie jakości życia [31,32] oraz obniżony nastrój [33], a każdego roku jest hospitalizowanych 10-40% pacjentów z AF [23,34,35]. Bezpośrednie koszty AF stanowią już w przybliżeniu 1% wszystkich wydatków na opiekę zdrowotną w Wielkiej Brytanii, a w Stanach Zjednoczonych w 2008 roku wyniosły 6-26 mld dolarów [36,37], co wynika z powikłań związanych z AF (np.…”
Section: Zgonunclassified